Moderasi Beragama dalam Bernegara dan Fenomena Ragam Keyakinan dalam Keluarga - M. Samsul Ma'arif (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2024)
Diversity is an inevitability and a phenomenon that cannot be ignored. Diversity creates its own challenges, including diversity and differences in beliefs. Religion is a very sensitive belief and often touches the emotional dimension of individuals. When these differences are not managed wisely, they will easily trigger conflict, becoming the root of divisions including state and family relations. This research was carried out using a qualitative literature study method which aims to describe and analyze how moderate attitudes are needed in national life and the phenomenon of various beliefs in a family. As a result of research, a moderate attitude in responding to diversity is needed. And when a multi-religious family is able to prove that diverse beliefs are not the root of division, then that family deserves to be an example. The right role model for families that are already